(untitled) (BIOM - Revue scientifique pour la biodiversité du Massif central, 2025)
Corydalis intermedia (L.) Mérat is reported in the Ardèche department (07), in the Mézenc massif. Brief information of a chorological, historical, and ecological nature is provided regarding its presence in the Massif central.